Relationship between media and audiences in WhatsApp groups in Cuba: an approach from the agenda setting - Muñiz Zuñiga, Viviana (2023)
The study aims to explain the relationship between the agenda of the Sierra Maestra newspaper in Santiago de Cuba and that of its readers through two WhatsApp groups created by the newspaper from June to October 2021. A quantitative research design was employed using techniques such as content analysis in the selected groups and applied survey in their members. The study determined that there is no thematic relationship between the newspaper’s agenda and that of its readers. This is influenced by the little involvement of journalists in solving the problems of the group members, the slight possibility of criticizing in that space, the insufficient feedback between the country’s social institutions and the readers, and the ineffective role of journalists as informers. This analysis is part of a series of studies on the agenda-setting in Cuban WhatsApp groups and delves into the need to efficiently use this platform according to the media.